(untitled) (SAARC Journal of Agriculture, 2022)
It is necessary to assess genetic diversity and a molecular characteristic among Bangladesh’s local rice cultivars. The purpose of the study was to assess the genetic diversity and molecular characterization of 83 rice landraces in Bangladesh using nine (9) SSR markers. A total of 262 allels were identified using nine (9) polymorphic markers. The highest number alleles 34 were identified by RM336 while the lowest was 13 by RM262. Polymorphism information content (PIC) value of each marker was evaluated on the basis of the number of alleles and it varied greatly for all the SSR loci tested. The PIC value ranged from 0.951 to 0.766 and marker RM336 was found to be the most appropriate marker to discriminate among the rice genotypes owing to the highest PIC value of 0.951. The allele frequency ranged from 37.35% (RM262) to 10.84% (RM585, RM336) with an average of 18.47%. The genotypes G82, G77, G68, G50, and G1; G65, G37, and G10; G71 and G11; G25 and G14; G39 and G27 have 100% genetic similarity according to the pair wise genetic similarity indexes. Genotype G10 had the least similarity (0.44 percent) to genotype G9, G16 with G17, G22 with G29, G28 with G30, and so on. The dendrogram based on UPGMA and Nei’s genetic distance classified the 83 rice landraces into 5 clusters with a similarity coefficient of 0.6 Cluster 2 had maximum thirty-two genotypes followed by cluster 4. The landraces that were derivatives of genetically similar types were clustered together on the dendrogram. These landraces is showed wide genetic divergence among the constituent in it and in future it will be useful for hybridization programme in plant breeding. SAARC J. Agric., 19(2): 13-25 (2021)